Atrial Septal Defect Closure via Left Subclavian Vein Approach in a Patient With Absent Inferior Vena Cava. Issue 1 (January 2022) - Enta, Yusuke; Tatebe, Shunsuke; Saiki, Yoshikatsu; Tada, Norio
Without the femoral venous approach, transcatheter closure of an atrial septal defect is challenging. We performed percutaneous closure via the left subclavian vein in a patient with absence of the inferior vena cava with azygos continuation. Considering that inferior vena cava anomalies are not extremely rare among those with congenital heart disease, the left subclavian vein approach can be an alternative to the femoral approach.